Diabetic nephropathy: newer therapeutic perspectives. Issue 4 (4th July 2018) - Keri, Krishna C.; Samji, Naga S.; Blumenthal, Samuel
ABSTRACT: Diabetic nephropathy (DN is a dreaded consequence of diabetes mellitus, accounting for about 40% of end-stage renal disease (ESRD). It is responsible for significant morbidity and mortality, both directly by causing ESRD and indirectly by increasing cardiovascular risk. Extensive research in this field has thrown light on multiple pathways that can be pharmacologically targeted, to control or reverse the process of DN. Glomerulocentric approach of DN still continues to produce favourable results as evidenced by the recent data on SGLT-2 (sodium glucose co-transporter type 2) inhibitors. Beyond the glomerular mechanisms, numerous novel pathways have been discovered in the last decade. Some of these pathways target inflammatory and oxidative damage, while the others target more specific mechanisms such as AGE-RAGE (advanced glycation end products-receptors for advanced glycation end products), ASK (apoptotic signal-regulating kinase), and endothelin-associated pathways. As a result of the research, a handful of clinically relevant drugs have made it to the human trials which have been elucidated in the following review, bearing in the mind that there are many more to come over the next few years. Ongoing research is expected to inform the clinicians regarding the use of the newer drugs in DN. Abbreviations: USFDA: Unites States Food and Drug Administration; SGLT-2: Sodium glucose transporter type 2; GLP-1: Glucagon-like peptide-1; DDP-4: Dipeptidyl peptidase-4; UACR: urinary albumin creatinine ratio; eGFR: Estimated glomerular filtration rate; CKD: Chronic kidney disease; DN: Diabetic nephropathy; TGF: Tubuloglomerular feedback; RAAS: Renin angiotensin aldosterone system; T1DM: Type 1 diabetes mellitus; T2DM: Type 2 diabetes mellitus; RCT: Randomized controlled trial; AGE-RAGE: Advanced glycation end products-receptors for advanced glycation end products; ASK-1: Apoptotic signal-regulating kinase-1; Nrf-2: Nuclear 1 factor [erythroid derived-2]-related factor 2; ml/min/1.73m 2 : Millilitre/minute/1.73 square meters of body surface area; ~: Approximately.